1991
DOI: 10.1677/joe.0.1280333
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular dehydration in the rat made diabetic with streptozotocin: effects of infusion

Abstract: Metabolic and isotopic dilution techniques were used to investigate fluid balance and fluid volumes in rats made diabetic with streptozotocin before and after infusion. Uninfused diabetic rats had significantly (P less than 0.01) lower total body water than controls (57.7 +/- 2.2 vs 65.7 +/- 1.4% (S.E.M.) fat free mass). This was due exclusively to a significantly (P less than 0.001) reduced intracellular fluid volume (38.2 +/- 1.5 vs 45.4 +/- 1.4% fat free mass). Metabolic studies over the preceding 2 weeks s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…It has been suggested that plasma protein binding of drugs may change because of change in plasma fatty acid levels [9]. Moreover, an intracellular dehydration has been observed in male Sprague-Dawley DMIS rats [24]. Consequently both may affect the distribution of drugs in the body.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that plasma protein binding of drugs may change because of change in plasma fatty acid levels [9]. Moreover, an intracellular dehydration has been observed in male Sprague-Dawley DMIS rats [24]. Consequently both may affect the distribution of drugs in the body.…”
Section: Resultsmentioning
confidence: 99%
“…In diabetic rats insulin deficiency causes severe changes in metabolism among others, a reduction in liver protein synthesis, decreased activity of the sympathetic nervous system, dehydration, glycosuria, and osmotic diuresis (28,29). Thus, streptozotocin-diabetic rats showed a different response profile to environmental stress factors (30).…”
Section: Diabetic Ratsmentioning
confidence: 99%
“…5,22 Values recorded from our rats clearly represent an overestimate of the animal's natural excretion rate and probably result from a volume expansion produced by the high constant infusion. 23 If they are infused at a rate below that of their natural fluid intake or urine output, fluid is retained rather than excreted in an attempt to restore intracellular volume. 5 When our diabetic rats were similarly infused, their urine output stabilized at 106Ϯ13 L/min, contrasting with rates of approximately twice this value reported in non-infused diabetic animals.…”
Section: Servo-controlled Protocolmentioning
confidence: 99%